"If you keep your problems in your stomach the dogs cannot steal them" : trauma, forgiveness, and con-viviality in Rwanda : an ethnographic study following the healing and rebuilding our communities (HROC) project in Gisenyi, Rwanda - Forcier, Angela (Social Anthropology, 2015)
Includes abstract.